Efficacy and Tolerability of Cosmetic Serums Enriched with Five Forms of Hyaluronic Acid as Part of Biweekly Diamond Tip Microdermabrasion Treatments for Facial Skin Dryness and Age-Associated Features - Makino ET; Huang PC; Emmerich T; Jiang LI; Mehta RC (Dove Medical Press, 2023)
Elizabeth T Makino,1 Priscilla C Huang,1 Tanja Emmerich,2 Lily I Jiang,2 Rahul C Mehta1 1SkinMedica - Allergan Aesthetics, an AbbVie Company, Irvine, CA, USA; 2SGS Stephens Inc, Richardson, TX, USACorrespondence: Elizabeth T Makino, SkinMedica - Allergan Aesthetics, an AbbVie Company, 18581 Teller Ave, Irvine, CA, 92612, USA, Tel +1 714 246-2598, Email elizabeth.makino@abbvie.comPurpose: There is growing interest in combining topical treatments with aesthetic procedures to combat signs of aging skin. This study aimed to assess the efficacy and tolerability of a novel cosmetic serum containing 5 different forms of HA (HA5 DG) when used via a proprietary diamond-tip microdermabrasion procedure (DG) to treat skin dryness, fine lines/wrinkles, rough texture, and dullness.Patients and Methods: In this open-label, single-center study, participants received HA5 DG as part of a biweekly DG procedure on the face and neck for 12 weeks. Study participants also applied another take-home HA5 serum to the face twice daily at home, along with a basic skincare regimen. The efficacy of the combined treatment was measured by clinical quantification of multiple skin appearance features, analysis of bioinstrumental measurements, and digital photography.Results: This study enrolled 27 participants, with an average age of 42.7 years and Fitzpatrick skin phototypes I-III (59.3%), IV (18.5%), and V-VI (22.2%), and 23 participants completed the study. The combined treatment had effects in fine lines/wrinkles, skin dryness, smoothness, radiance, firmness, and hydration 15 minutes post-DG. Furthermore, the significant improvements observed in dryness, fine lines/wrinkles, skin smoothness, and radiance were still visible 3 days after and maintained at week 12. Additionally, smoothing of coarse lines/wrinkles, improvement of skin tone evenness, hyperpigmentation, photodamage, and transepidermal water loss were observed at week 12. The treatment had a favorable tolerability profile and was perceived as efficacious and highly satisfactory.Conclusion: This novel combined treatment delivered immediate and prolonged skin hydration and high participant satisfaction, proving it can be an excellent approach for skin rejuvenation.Keywords: microdermabrasion, skin aging, hyaluronic acid, combined treatment, facial rejuvenation, skin dryness